Biografi Nabi Muhammad SAW Masa di Makkah dan Madinah Hingga Wafat - Ifriani, Ifriani; Misran, Misran; Rama, Bahaking (CV. Ulil Albab Corp, 2024)
In a time of political, economic, social, and religious turmoil in both the West and the East, a timeless figure was born who built the power of Islam between two great world empires, in the Arabian Peninsula as a mercy to all mankind, that is Prophet Muhammad SAW. It has been mentioned that the Arab society was filled with darkness, including those who worshipped idols of their own making. Prophet Muhammad was sent with a prophetic mission, teaching that there is no god but Allah, who knows all the actions of mankind and will reward or punish accordingly in the afterlife. The greatness of Prophet Muhammad and his companions is truly remarkable, and therefore, the author will present an article that contains the biography of Prophet Muhammad and the histories of developing, spreading, and advancing the Islamic religion. May the biography of Prophet Muhammad demonstrate the spirit of struggle possessed by him and his companions in upholding the faith.